Conceptual Models of Ecological Metaphors in English Discourse - Gulomjonova, Nozigul Dilshodbek qizi (The Lingua Spectrum, 2026)
This article examines English ecological discourse metaphors from a linguocognitive perspective. The study is based on the assumption that metaphor is not merely a stylistic device, but a cognitive mechanism through which ecological reality is conceptualized and interpreted. The article identifies the dominant conceptual models that structure English ecological discourse and analyzes their metaphorical networks, frames, and slots. Special attention is paid to such models as NATURE IS A LIVING ORGANISM, THE PLANET IS A BODY, CLIMATE CHANGE IS WAR, THE EARTH IS HOME, and NATURE IS A SYSTEM. The research demonstrates that these metaphorical models play an important role in the cognitive organization of environmental knowledge and in the linguistic representation of ecological problems. The findings show that English ecological discourse relies on stable metaphorical patterns that make complex environmental phenomena more understandable, emotionally significant, and socially relevant. The results of the study may be used in cognitive linguistics, ecolinguistics, discourse analysis, and further comparative research on ecological metaphors.